Crossing Suture Technique for the Osteochondral Fractures Repair of Patella - Ng, W.M.; Al-Fayyadh, M.Z.M.; Kho, J.; Teo, S.H.; Mohamed Ali, M.R. (Elsevier, 2017)
Osteochondral fracture of the patella is a common concomitant injury of the knee, especially in lateral patellar instability, and the importance of early stable fixation with minimal complication and early mobilization should be emphasized. Screws and Kirschner wires both absorbable and nonabsorbable have been the common mode of fixation of these fractures. Nevertheless, these fixation techniques require larger osteochondral fragments and are associated with cartilage abrasion, hardware prominence, synovitis, and foreign body reaction. In contrast, suture fixation can adequately stabilize smaller osteochondral fragments without comminution and prevent some of the possible complications of other techniques of fixation. We created 4 holes in a rectangular pattern on the patella oriented perpendicular to its anteroposterior surface. We used readily available, and affordable, no. 2 Ultrabraid sutures inserted into the holes and looped around the osteochondral fragment, compressing it to the patella. The technique is very simple and is relatively easy to learn. It provides secure fixation and allows early mobilization. And it spares the knee from subsequent surgical procedure for removal of metallic implants.